2017
DOI: 10.1016/j.amsu.2017.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Is In-Vivo laparoscopic simulation learning a step forward in the Undergraduate Surgical Education?

Abstract: BackgroundEssentials Skills in the Management of Surgical Cases – ESMSC is an International Combined Applied Surgical Science and Wet Lab course addressed at the Undergraduate level. Laparoscopic Skills is a fundamental element of Surgical Education and various Simulation-Based Learning (SBL) models have been endorsed. This study aims to explore if there is any significant difference in delegates' performance depending on whether they completed In Vivo module prior to the equivalent in the laparoscopic simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…No difference was noted in any performance outcome across different years of study ( Table 1 , p > 0.05 for any association). Whilst our small sample size may limit the power of our analysis, previous experiences with the course [ 8 , 20 ], alongside other studies [ 21 ] support this finding. We feel this may represent a lack of exposure to practical surgical teaching in undergraduate surgical education which should be addressed further in larger scale prospective studies.…”
Section: Discussionsupporting
confidence: 50%
“…No difference was noted in any performance outcome across different years of study ( Table 1 , p > 0.05 for any association). Whilst our small sample size may limit the power of our analysis, previous experiences with the course [ 8 , 20 ], alongside other studies [ 21 ] support this finding. We feel this may represent a lack of exposure to practical surgical teaching in undergraduate surgical education which should be addressed further in larger scale prospective studies.…”
Section: Discussionsupporting
confidence: 50%
“…It combines high and low fidelity in vivo, ex vivo and dry lab simulation modules with applied surgical science and basic knowledge interactive workshops. The current curriculum (cores integrated for research—Ci4R) is set up in an ergonomic way to combine 40 learning modules which promote multidisciplinary learning strategies and facilitate various research projects as part of the course [6, 24, 26–28]. This concept has been previously described [27], and it has received accreditation by the European Council for Continuous Medical Education (EACCME).…”
Section: Methodsmentioning
confidence: 99%
“…There is also the question of whether these simulations are realistic. Pantelidis et al 8 showed that these dry-lab simulations can be as efficacious as porcine models, and this is corroborated by Shaharan and Neary 7 . In addition, at the undergraduate level in particular, haptic feedback is not necessary for the development of a similar skillset, as evidenced by Pantelidis and colleagues.…”
mentioning
confidence: 75%
“…They used 2 groups of students, and had them participate in both groups, either in vivo first or the dry-lab simulation first. They concluded that high-fidelity in vivo simulation does not significantly improve results in comparison with dry-lab simulation 8 .…”
mentioning
confidence: 99%